The follower of flowers eaudiobook - Hernandez, Natalia (Flowers of Prophecy, 2023)
As a child, the Name-Bearer had one duty; to receive and deliver the names of the future monarchy from the Flowers of Prophecy. But on the day of the Naming Ceremony, the Flowers refused. They claim another child was born more worthy of the Naming, and the Name-Bearer must find him and deliver him to them in order to restore peace to her land. Now, ten years later, the Name-Barer and her companions are on a quest to find the Unnamed Prince and fulfill the prophecy. But with a bounty on their heads, an increase in monstro activity, and a long dangerous journey through enemy territory, they may be in for more than they bargained for. In order to survive, they will have to rely on strangers, unlikely new allies, and those they once loved—and hope that their trust in them has not been misplaced. With so much opposition, will their courage—and their friendships, survive?